1990
DOI: 10.1111/j.1745-9125.1990.tb01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification to Halfway Houses: A Quasi‐experimental Evaluation *

Abstract: Faced with prison overcrowding, institutions must seek alternatives to imprisonment. An underresearched possibility is the use of haljivay houses for the placement of oflenders serving prison sentences. The LSI, an objective risk classijication instrument, was administered to inmates from three jails. Low-scoring inmates from two of the jails were flagged for placement in correctional haljivay houses, and the third jail was blind to LSI scores. The haljivay house placement rate was 51 % for the jails that used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…Inter-rater reliability coefficients range from 0.80 to 0.96 (Andrews and Bonta, 1995). Validity studies indicate that elevated LSI-R scores of offenders residing in halfway houses are indicative of parole violations and returning to prison (Motiuk et al, 1986;Bonta and Motiuk, 1990). Research has shown that those with high LSI-R scores have a greater likelihood of reoffending (Bonta andMotiuk, 1987, 1992).…”
Section: Participants and Proceduresmentioning
confidence: 96%
“…Inter-rater reliability coefficients range from 0.80 to 0.96 (Andrews and Bonta, 1995). Validity studies indicate that elevated LSI-R scores of offenders residing in halfway houses are indicative of parole violations and returning to prison (Motiuk et al, 1986;Bonta and Motiuk, 1990). Research has shown that those with high LSI-R scores have a greater likelihood of reoffending (Bonta andMotiuk, 1987, 1992).…”
Section: Participants and Proceduresmentioning
confidence: 96%
“…It has acceptable internal consistency and temporal stability (Bonta & Motiuk, 1990, 1992. LSI subscale scores have demonstrated convergent validity with alternative measures of the same construct (Andrews, 1982;Andrews, Kiessling, Mickus, & Robinson, 1986) and dynamic validity as reassessments result in improved prediction (Andrews & Robinson, 1984).…”
Section: History Of Lsimentioning
confidence: 96%
“…judgment and expertise of staff, but such systems have proven inconsistent, often resulting in biased and arbitrary assessments (Alexander, 1986;Bonta & Motiuk, 1990). Objective instruments help standardize staff classifications and produce more consistent and fair decisions.…”
mentioning
confidence: 99%